THE OCCURRENCES OF WTC AMONG MALAYSIAN PRE-UNIVERSITY STUDENTS IN AN ESL ONLINE CLASSROOM - Anna Lynn Abu Bakar (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
The English language is regarded as an important mode of communication in Malaysia, particularly in higher education institutions and the workplace. The perception that graduates lack English communication skills renders them unemployable upon graduation. Therefore, a great deal of effort has been expended to produce students who can communicate effectively in a variety of social and professional settings. The Ministry of Education has taken numerous steps to improve the English proficiency of students. This study examines pre-university students’ willingness to communicate (WTC) in a digital setting at a local university. This study employed a qualitative methodology and included 12 classroom observations. The classroom observation data was subjected to an inter-rater reliability analysis, and the results revealed that the mood and role of the English Language Instructors (ELIs) significantly influenced the occurrences of WTC in English among pre-university students. The findings of this study are intended to provide stakeholders, curriculum developers, and ELIs with a better understanding of the teaching and learning factors that must be considered in order to ensure students’ WTC in English.